Child rearing practices in a rural community in Manipur: a cross-sectional study - Singh, Haobam Danny; Keisam, Avinash; Rajkumari, Bishwalata (International Journal Of Community Medicine And Public Health, 2019)
Background: The child rearing practices differ in communities, depending on their social customs, traditional beliefs and prejudices. Understanding these practices is important for the successful delivery of health messages and services. The present study was conducted in a rural setting to determine the child rearing practices as well as to determine its association with relevant socio-demographic factors. Methods: This cross-sectional study was conducted among 369 mothers residing in Kshetrigao area under Kshetrigao Urban Health Centre, Porompat, Imphal East. A pre-tested interview schedule developed by the investigator was used for data collection. Descriptive statistics like mean, percentage and proportion as well as chi-square and t-test were used for data analysis. Results: Majority (79%) of the mothers breast-fed their newborn within 6 hours after birth. Almost half (46%) of the mothers gave pre-lacteal feeds to their newborn. Majority of the mothers (57%) did not practice exclusive breastfeeding. About 90% of the children were completely immunized for age. Mothers who got married before the age of 20 years, being Muslim and who had caesarean section were significantly less likely to practice exclusive breast feeding (p value of 0.025, 0.012 and 0.000 respectively). Children whose mother belongs to Muslim religion, lower educational status, lower family income and who delivered at home were significantly less likely to be completely immunized (p value of 0.001, 0.003, 0.014 and 0.003 respectively). Conclusions: Giving pre-lacteal feed and not practicing exclusive breast-feeding were very common among the studied population.